(3GdeSGQ GdGeQjcj h GdHhQUGJ GdfGTFIs - (3LdGd(B, (3GdHfGs ((3eUQ(B:s (3TQcI GdfOi(B,s, 2007)
(3CfhGY GdGhQGb GdeGdjI , GdeNGWQI h GdecGaCI h JUeje GdhQbI GdeGdjI , GdSge GdYGOj h GdGhQGb GdeGdjI GdOGfFI , CSGSjGJ ddSfOGJ , GdGhQGb GdeGdjI PGJ GdONd GdKGHJ h PGJ GdONd GdeJZjjQ , GdGUaGQ h GdeJMhdGJ , GdGSge GdeeJGRI , GdGhQGb GdeGdjI ddMcheI GdGeQjcjI h GdGhQGb GdeGdjI GdfGbdI ddJOabGJ GdfbOjI , JYRjRGJ GdGFJeGf , GdGhQGb GdeGdjI GdfGbdI ddJOabGJ GdfbOjI (B: (3GdMchejI h GdTHg MchejI h GdOaYGJ GdGhdjI , GYWGA QJH ddSfOGJ , OhQ CefGA GdGSJKeGQ aj GdGhQGb GdeGdjI h GdWQM GdGhdj ddLeghQ , Mbhb GdJUhjJ h GdfahP , GdGSge GdYGOjI GdeJNUUI , GdMbhb GdGLgGVjI , eDSSI GdGMJcGQGJ GdGSJKeGQjI GdYbGQjI h eDSSI GdJjSjQGJ GdGSJKeGQjI ddQgf GdYbGQj , Jbjje GdGhQGb GdeGdjI , GdJMdjd GdGSGSj h GdJMdjd Gdafj , GdeTi GdYThGFj , GdHjJG (B((3ebjGS ddeNGWQ GdefJXeI(B)(3, GdeTQhYGJ GdhgejI , GdGMJjGd h GdMeGbGJ , GdTQGA h GdHjY , GdTgGOGJ h GdbjO GdOaJj , GdJMhW , UfGOjb GdGSJKeGQ hhMOI GdJhUjI GdeMOhOI GdGSJKeGQjI , GdHhQUGJ , GdShb GdeZdbI ddGSge , GdbhGfjf GdajOjQGdjI GdQFjSjI ddGhQGb GdeGdjI (B: (3GdbGfhf (B33(3, GdbGfhf (B34(3, GdbGfhf(B40 (3h JTQjYGJ CNQi(B.s
(3eYLe GdeUWdMGJ U(B.137(3; edGMb U(B.163s
Keywords: (3GdGSJKeGQs; (3GdGhQGb GdeGdjIs; (3GdSfOGJs